2015
DOI: 10.1111/crj.12384
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors that influence anxiety and satisfaction in patients undergoing bronchofiberoscopy with analgosedation

Abstract: Patients who had previously undergone BF were better prepared for their procedure; however, satisfaction levels after the procedure were similar in both groups. Results suggest that medical staff should target patients who have not undergone BF previously to relieve anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
5
1
1
Order By: Relevance
“…[9] Furthermore, it has been reported that prior experience of bronchoscopy helps in reducing anxiety levels and makes patients better prepared for the procedure. [30] However, we did not find prior experience of bronchoscopy a significant predictor in our analysis. While this study sheds light on several interesting aspects related to the predictors of anxiety in patients undergoing bronchoscopy, it also possesses the potential to influence patient management and willingness to undergo the procedure again in the future.…”
Section: Discussioncontrasting
confidence: 63%
“…[9] Furthermore, it has been reported that prior experience of bronchoscopy helps in reducing anxiety levels and makes patients better prepared for the procedure. [30] However, we did not find prior experience of bronchoscopy a significant predictor in our analysis. While this study sheds light on several interesting aspects related to the predictors of anxiety in patients undergoing bronchoscopy, it also possesses the potential to influence patient management and willingness to undergo the procedure again in the future.…”
Section: Discussioncontrasting
confidence: 63%
“…Although it is certainly necessary to minimize discomfort during bronchoscopy, it cannot be eliminated. In previous studies investigating factors that influence anxiety and satisfaction experienced by patients undergoing bronchoscopy, patients who showed willingness to be re-examined and underwent multiple bronchoscopies were on average more satisfied with their physicians’ explanations of the procedure [10,11]. Although patients fear a variety of things before bronchoscopy, such as pain, breathing difficulties, and oropharyngeal irritation, doctors tend to explain "why" but not "how" the procedure is performed [7].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 8 out if the 20 patients did have a previous bronchoscopy. The influence of a previous bronchoscopy on the level of anxiety is debated in the literature, with contradictory results(2,19). In the future, a controlled study could also analyze the effect of a previous bronchoscopy, with or without VRH, on anxiety.…”
mentioning
confidence: 99%